Ventricular Repolarization is Associated with Cognitive Function, but Not with Cognitive Decline and Brain Magnetic Resonance Imaging (MRI) Measurements in Older Adults - Zonneveld, Michelle H. (J Clin Med, 2020)
We aimed to investigate the cross-sectional and longitudinal associations of electrocardiogram (ECG)-based QT, QTc, JT, JTc, and QRS intervals with cognitive function and brain magnetic resonance imaging (MRI) measurements in a cohort of older individuals at increased risk for cardiovascular disease, but free of known arrhythmias. We studied 4627 participants (54% female, mean age 75 years) enrolled in the Prospective Study of Pravastatin in the Elderly at Risk (PROSPER). Ten-second ECGs were conducted at baseline. Cognitive function was tested at baseline and repeated during a mean follow-up time of 3.2 years. Structural MRIs were conducted in a subgroup of 535 participants. Analyses were performed with multivariable (repeated) linear regression models and adjusted for cardiovascular risk-factors, co-morbidities, and cardiovascular drug use. At baseline, longer QT, JT, JTc—but not QTc and QRS intervals—were associated with a worse cognitive performance. Most notably, on the Stroop Test, participants performed 3.02 (95% CI 0.31; 5.73) seconds worse per standard deviation higher QT interval, independent of cardiovascular risk factors and medication use. There was no association between longer ventricular de- or repolarization and structural brain measurements. Therefore, specifically ventricular repolarization was associated with worse cognitive performance in older individuals at baseline but not during follow-up.